Evaluasi Kinerja Arsitektur Web Berbasis Single Page Application Pada Aplikasi Presensi Kuliah - Sadikin, Ali; Rahim, Abdul; Wardani, Muhammad; Irawan (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2026)
The evolution of interactive web applications has popularized server-driven approaches like Livewire as an alternative for developing Single Page Applications (SPA) without complex JavaScript dependencies. However, the performance implications of this approach compared to conventional methods require empirical evaluation. This study compares the performance of Laravel Blade (Traditional/AJAX) and Livewire within the context of an academic attendance system. Testing was conducted using k6 for load simulation and browser-based analysis to observe actual communication patterns. Load testing results indicate that Livewire has an average response time 2.7× higher and bandwidth consumption up to 6× greater due to the state snapshot mechanism. However, browser interaction tests reveal the architectural superiority of Livewire’s SPA model, which reduced HTTP requests by 88.1% and navigation data load by 78.7% by eliminating full page reloads. Furthermore, Livewire demonstrated superior stability with a 0% error rate compared to Blade (0.69%). These findings indicate that while per-request overhead exists, Livewire offers better network resource efficiency during sustained use and more consistent stability for interactive applications